Business ethics - Khalidah Khalid Ali 1956-; Zulkufly Ramly 1971-; Lau, Teck Chai 1969- (Oxford Fajar Sdn Bhd, 2014)
Business Ethics is intended for undergraduate students pursuing business and accountancy courses at local institutions of higher learning. It discusses business ethics in depth from a local perspective. The book opens with discussions on the key concepts and theories of business ethics, followed by important topics such as corporate governance, corporate social responsibility and sustainability. Additional topics covered include consumer ethics and ethics from an Islamic perspective. To help students relate what they have learnt to the real world, topics are punctuated with authentic cases for review.